2019
DOI: 10.5152/jarem.2019.2319
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Assisted Osteosynthesis of Distal Radius Intra-articular Fractures

Abstract: Radius alt uç eklem içi kırıklarında, anatomik eklem restorasyonu amacıyla, kırık redüksiyonu artroskopi yardımıyla fluoroskopi kontrolünde yapılarak, eşlik eden eklem içi patolojilerinin sıklığı ve şiddeti araştırılıp, prospektif olarak olguların sonuçları değerlendirildi. Yöntemler: Distal radius eklem içi kırığı olup, redüksiyon sağlanamayan veya instabil kırığı olan on iki erişkin hasta çalışmaya alındı. Eksternal fiksatör ile distraksiyon sağlandı. Eklem yüzeyi artroskopik gözlem altında restore edildikte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ünal et al (16) reported that volar plate applications yielded satisfactory mid-term results, despite longer operating time and hospital stay compared to external fixation. Özden et al (17) stated that intra-articular fractures can be evaluated and by arthroscopic methods and corrected. Stirling et al (18) stated that the RI angle is one of the most important parameters in the evaluation of bone displacement in distal radius fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Ünal et al (16) reported that volar plate applications yielded satisfactory mid-term results, despite longer operating time and hospital stay compared to external fixation. Özden et al (17) stated that intra-articular fractures can be evaluated and by arthroscopic methods and corrected. Stirling et al (18) stated that the RI angle is one of the most important parameters in the evaluation of bone displacement in distal radius fractures.…”
Section: Discussionmentioning
confidence: 99%